Training and Provision of Information Related to The Accessibility of Official Higher Education Institutions for High School Students of The Same Level in Pekalongan City - Arditya Prayogi; Ulfa Kurniasih; Ahmad Faridh Ricky Fahmy (Room of Civil Society Development, 2023)
Education plays a vital role in human life, serving as a means to achieve a high quality of life. Within the realm of formal education, higher education holds particular significance in enhancing the human resources of a nation and contributing to their continual improvement. The objective of this service initiative is to provide comprehensive information on the official college selection process and deliver training through entrance examination questionnaires, enabling participants to better equip themselves for the official college entrance examinations. This community service endeavor primarily utilizes socialization and facilitates access to official school information, achieved through collaboration with external service partners. Specifically, the "Neutron" tutoring institution in Pekalongan acts as a dedicated partner, actively engaging in discussions concerning official school entrance examination questions. The activity drew participation from 114 students representing various schools in Pekalongan. The outcomes of the community service activities showcased a high level of enthusiasm among the participants, evident in their positive response and active engagement throughout the program. This positive response was demonstrated by the participants' enthusiastic completion of practice questions, thereby reinforcing their preparation for the official college entrance examinations. Information dissemination and provision of practice questions aim to empower participants to adequately prepare for their future academic pursuits.